Lightweight architected lattice phononic crystals with broadband and multiband vibration mitigation characteristics. (November 2020) - Muhammad; Lim, C.W.; Li, Jensen T.H.; Zhao, Zhen
Abstract: A novel architected lattice metamaterial with broadband and multiband bandgap characteristics is studied here. A slight structural modification in a regular lattice structure has succeeded to significantly magnify the vibration attenuation capability of these lightweight periodic lattices. The vibration control properties of these lattices are investigated both theoretically and experimentally. The sinusoidal-shaped ligament is found useful in generating a broadband Bragg bandgap with robust wave attenuation characteristics. The embedment of circular masses at the center of these lattices help induce multiband low frequency bandgaps. The properties of sinusoidal-shaped ligament such as the number of sine wave undulations/ligament wavelength and the effect of central mass radius on bandgaps are investigated. Introducing material damping flattens the transmission peaks and it results in a broadband bandgap distributed throughout the frequency spectrum. The experimental results are in good agreement with numerical solutions. The proposed lightweight lattice metamaterial can be effectively applied at any length scale for controlling acoustic/elastic waves propagation. Graphical abstract: Highlights: A novel lightweight architected lattice periodic structure is proposed. SSL in proposed lattice helps generate broadband vibration attenuation zone. Vibration attenuation caused by broadband and multiband bandgaps are investigated. SSL and embedded central mass effects on bandgaps are studied. Experiment test is performed on 3D printed specimen for study validation.